Galectin-3 Attenuates Lipopolysaccharides-induced Inflammation in Adipocyte and Macrophage Co-culture System - Vemuri, Praveen Kumar (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Galectin-3 (Gal-3) expression act as a potential novel therapeutic strategy in the treatment of a broad range of inflammatory diseases. Aim: This study aims to study the cross-talk between macrophage and adipocyte cells with Gal-3 upon lipopolysaccharides (LPSs) challenge. Materials and Methods: Cytokine secretion in 3T3-L1 adipocyte-RAW 264.7 macrophage cells were greatly enhanced on LPS stimulation compared to isolated cell culture system, suggesting the cross-talk between these cell types during LPS exposure. Gene and protein expression profile was analyzed by reverse transcription-polymerase chain reaction for understanding the inflammatory responses. Results: Decreased expression of interleukin 6 was confirmed as lowered suppressor of cytokine signaling 3 expressions downstream. A critical appraisal of the role of nuclear factor-ÎºB (NF-ÎºB) in LPS induced alteration of inflammatory phenotype was confirmed as decreased formation of tumor necrosis factor-Î± transcript using specific inhibitors of NF-ÎºB, along with LPS treatment. Further, Gal-3 also inhibited nuclear p65 translocation, IkB-Î± degradation and induction of inducible nitric oxide synthase, in response to LPS. Conclusion: These results clearly suggest decreased oxidative burden and inflammation are significantly affected by Gal-3.